5(3x+2)-7=3(2x-5)

Simple and best practice solution for 5(3x+2)-7=3(2x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3x+2)-7=3(2x-5) equation:



5(3x+2)-7=3(2x-5)
We move all terms to the left:
5(3x+2)-7-(3(2x-5))=0
We multiply parentheses
15x-(3(2x-5))+10-7=0
We calculate terms in parentheses: -(3(2x-5)), so:
3(2x-5)
We multiply parentheses
6x-15
Back to the equation:
-(6x-15)
We add all the numbers together, and all the variables
15x-(6x-15)+3=0
We get rid of parentheses
15x-6x+15+3=0
We add all the numbers together, and all the variables
9x+18=0
We move all terms containing x to the left, all other terms to the right
9x=-18
x=-18/9
x=-2

See similar equations:

| 540xX=15 | | x/5=-11/6 | | 10y+7.9=29 | | 10b+2b=60 | | 4(x-3)=2(x+5)=4 | | -10x+9x-5=12 | | −10x+9x−5=12 | | 3x÷7=9 | | x/5+7/3=1/2 | | 3(2x-5)=4x+6-3x | | 2a^2+6a+4=0 | | 2x+3-9=-35 | | P+q=¼ | | 2-1/2n=3n+16 | | 17-x=48 | | 5(2x-2)=7x | | 22n-17=12n+8 | | (6.6/7.2)=(x/1) | | 6.6/7.2=x/1 | | 25-7y=28-4y | | 4x+4x=100 | | 2x+x=109 | | -3x+24-x-5=20 | | g+3½=10 | | 0.7*x+2.5*0.3=5 | | (a-8)=(a-6) | | 12=k-8/3 | | -3(x-8)-(x+5)=20 | | 5*a+2=6-7*a | | X=4t+6t-4t | | 10x15=65 | | x/2+1=1/4*x-6 |

Equations solver categories